Are Premature Birth and Low Birth Weight Associated with Delay on the Eruption of Deciduous Teeth? A Systematic Review and Meta-analysis - Paula Dresch Portella; Gisele Marchetti; Leticia Wambier; Juliana Feltrin de Souza; Fabian Calixto Fraiz; José Vitor Nogara Borges de Menezes; Luciana Reichert da Silva Assunção (Association of Support to Oral Health Research (APESB), 2023)
Objective: To investigate whether children with premature birth (PB) and/or with low birth weight (LBW) have different tooth eruption patterns than those born at term or with normal weight. Material and Methods: Searches were performed in the PubMed, Cochrane Library, Sc1opus, Web of Science, LILACS, and BBO databases as well as the grey literature. Three independent reviewers were involved in study selection, data extraction, and bias assessment. The risk of bias was assessed using the Modified Newcastle-Ottawa Scale. Meta-analysis was conducted to compute the mean difference (MD) in mean chronological or adjusted age at the eruption of the first deciduous tooth between preterm children and those born at full term. The GRADE approach was used. Results: Among a total of 316 articles identified, 21 were eligible for inclusion and three were included in the meta-analysis. PB was associated with the delay in the first tooth deciduous eruption when chronological age was considered (MD: 1.36; 95%CI: 1.02-1.69) but not when considering adjusted age (MD: -0.30; 95%CI: -0.67-0.07). The evidence was graded as having very low quality. Conclusion: Based on a low certainty of evidence the PB is associated with the delayed eruption of the first deciduous tooth when considering chronological age but not when adjusted age is considered.